2021
DOI: 10.1039/d0cb00142b
|View full text |Cite|
|
Sign up to set email alerts
|

Bypassing the requirement for aminoacyl-tRNA by a cyclodipeptide synthase enzyme

Abstract: Cyclodipeptide synthases recognize a minimalistic substrate to produce cyclic dipeptides in a tRNA-independent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…Previous research from our group highlighted the use of these molecules to produce CDPs however that particular enzyme -BtCDPS -only required one aa-DBE to give a product. 15 Herein we explore the use of a combination of both DBE and tRNA to yield cyclic products.…”
Section: Incorporation Of Non-canonical Amino Acids Into Cyclic Dipeptidesmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research from our group highlighted the use of these molecules to produce CDPs however that particular enzyme -BtCDPS -only required one aa-DBE to give a product. 15 Herein we explore the use of a combination of both DBE and tRNA to yield cyclic products.…”
Section: Incorporation Of Non-canonical Amino Acids Into Cyclic Dipeptidesmentioning
confidence: 99%
“…aa-DBE has a limited half-life, which also impacts reaction yields. 15 Mass spectrometry of BtCDPS indicated that the enzyme could form the first acyl-enzyme intermediate when a DBE substrate was used. 15 Docking simulations suggested the decreased product formation when aa-DBE is a substrate occurs due to the second substrate binding and unproductive positioning in P2, lacking essential residue interactions for the reaction to proceed.…”
Section: Cdp Formation Using a Minimal Substratementioning
confidence: 99%
See 3 more Smart Citations